Measurement of Soret and Fickian diffusion coefficients by orthogonal phase-shifting interferometry and its application to protein aqueous solutions - Torres, Juan F.; Komiya, Atsuki; Henry, Daniel; Maruyama, Shigenao (The Journal of chemical physics, 2013)
We have developed a method to measure thermodiffusion and Fickian diffusion in transparent binary solutions. The measuring instrument consists of two orthogonally aligned phase-shifting interferometers coupled with a single rotating polarizer. This high-resolution interferometer, initially developed to measure isothermal diffusion coefficients in liquid systems [J. F. Torres, A. Komiya, E. Shoji, J. Okajima, and S. Maruyama, Opt. Lasers Eng. 50, 1287 (2012)], was modified to measure transient concentration profiles in binary solutions subject to a linear temperature gradient. A convectionless thermodiffusion field was created in a binary solution sample that is placed inside a Soret cell. This cell consists of a parallelepiped cavity with a horizontal cross-section area of 10 × 20 mm2, a variable height of 1–2 mm, and transparent lateral walls. The small height of the cell reduces the volume of the sample, shortens the measurement time, and increases the hydrodynamic stability of the system. An additional free diffusion experiment with the same optical apparatus provides the so-called contrast factors that relate the unwrapped phase and concentration gradients, i.e., the measurement technique is independent and robust. The Soret coefficient is determined from the concentration and temperature differences between the upper and lower boundaries measured by the interferometer and thermocouples, respectively. The Fickian diffusion coefficient is obtained by fitting a numerical solution to the experimental concentration profile. The method is validated through the measurement of thermodiffusion in the well-known liquid pairs of ethanol-water (ethanol 39.12 wt.%) and isobutylbenzene-dodecane (50.0 wt.%). The obtained coefficients agree with the literature values within 5.0%. Finally, the developed technique is applied to visualize biomolecular thermophoresis. Two protein aqueous solutions at 3 mg/ml were used as samples: aprotinin (6.5 kDa)-water and lysozyme (14.3 kDa)-water. It was found that the former protein molecules are thermophilic and the latter thermophobic. In contrast to previously reported methods, this technique is suitable for both short time and negative Soret coefficient measurements.